Drug selection based on pan-genomics genetic features of Mycobacterium tuberculosis - Sun, Xiangcheng; Xu, Panpan; Shi, Yun; Wang, Ning; Li, Yan (Frontiers in Microbiology, 2025)
Tuberculosis, caused by Mycobacterium tuberculosis, is a severe and persistent global public health issue, particularly exacerbated by the emergence of multidrug-resistant and extensively drug-resistant strains. This study employed pan-genomic approaches to analyze different strains with various resistance profiles, examining the diversity of bacterial genetic evolution in relation to mutations in resistance-related genes. The findings indicate that resistance-related genes are mostly core genes (94%), with a preference for base mutations closely associated with nonsynonymous mutations at resistance sites. Interestingly, while the majority of drugs induce positive selection in target genes, the tlyA gene under the influence of amikacin (AMI) undergoes passive selection. Cluster analysis of target genes suggests consistency between SNP clusters and drug-resistant clusters, revealing a strong correlation between bacterial evolutionary branches and resistance profiles. Consequently, based on pan-genome evolutionary characteristics, we identified the drug-resistant mutation pattern (DRMP) that can serve as a molecular fingerprint and indicator for drug sensitivity, aiding in the assessment and guidance of drug selection for treating different strains and the formulation of individualized treatment plans. This research not only enhances our understanding of the mechanisms of drug resistance in M. tuberculosis but also offers new perspectives for the development of new drugs, which is crucial for global tuberculosis control.